Genome Comparisons of Candida glabrata Serial Clinical Isolates Reveal Patterns of Genetic Variation in Infecting Clonal Populations - Carreté, Laia; Ksiezopolska, Ewa; Gómez-Molero, Emilia; Angoulvant, Adela; Bader, Oliver; Fairhead, Cécile; Gabaldón, Toni (Frontiers in Microbiology, 2019)
Candida glabrata is an opportunistic fungal pathogen that currently ranks as the second most common cause of candidiasis. Although the mechanisms underlying virulence and drug resistance in C. glabrata are now starting to be elucidated, we still lack a good understanding of how this yeast adapts during the course of an infection. Outstanding questions are whether the observed genomic plasticity of C. glabrata plays a role during infection, or what levels of genetic variation exist within an infecting clonal population. To shed light onto the genomic variation within infecting C. glabrata populations, we compared the genomes of 11 pairs and one trio of serial clinical isolates, each obtained from a single patient. Our results provide a catalogue of genetic variations existing within clonal infecting isolates, and reveal an enrichment of non-synonymous changes in genes encoding cell-wall proteins. Genetic variation and the presence of non-synonymous mutations and copy number variations accumulated within the host, suggest that clonal populations entail a non-negligible level of genetic variation that may reflect selection processes that occur within the human body. As we show here, these genomic changes can underlie phenotypic differences in traits that are relevant for infection.